2020
DOI: 10.3390/brainsci10110854
|View full text |Cite
|
Sign up to set email alerts
|

Strategy-Specific Patterns of Arc Expression in the Retrosplenial Cortex and Hippocampus during T-Maze Learning in Rats

Abstract: The retrosplenial cortex (RSC) belongs to the spatial memory circuit, but the precise timeline of its involvement and the relation to hippocampal activation have not been sufficiently described. We trained rats in a modified version of the T maze with transparent walls and distant visual cues to induce the formation of allocentric spatial memory. We used two distinct salient contexts associated with opposite sequences of turns. Switching between contexts allowed us to test the ability of animals to utilize spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Findings from a very different type of behavioural task, contextual fear conditioning, also implicate both the hippocampus (including the dorsal subiculum) and retrosplenial cortex in learning about space (Anagnostaras et al, 2001; Keene & Bucci, 2008; de Melo et al, 2020; Miller et al, 2014; Pan et al, 2022; Smith et al, 2012). Meanwhile, immediate‐early gene analyses indicate that the two regions have complementary roles in spatial tasks (Czajkowski et al, 2020; Frankland & Bontempi, 2005). In addition, neuronal recordings suggest that the hippocampus may encode and help distinguish contexts, while the retrosplenial cortex may enable behaviourally significant cues to identify the current context (Smith et al, 2012) or help predict future navigational decisions (Miller et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a very different type of behavioural task, contextual fear conditioning, also implicate both the hippocampus (including the dorsal subiculum) and retrosplenial cortex in learning about space (Anagnostaras et al, 2001; Keene & Bucci, 2008; de Melo et al, 2020; Miller et al, 2014; Pan et al, 2022; Smith et al, 2012). Meanwhile, immediate‐early gene analyses indicate that the two regions have complementary roles in spatial tasks (Czajkowski et al, 2020; Frankland & Bontempi, 2005). In addition, neuronal recordings suggest that the hippocampus may encode and help distinguish contexts, while the retrosplenial cortex may enable behaviourally significant cues to identify the current context (Smith et al, 2012) or help predict future navigational decisions (Miller et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a very different type of behavioural task, contextual fear conditioning, also implicate both the hippocampus (including the dorsal subiculum) and retrosplenial cortex in learning about space (Anagnostaras et al, 2001;Keene & Bucci, 2008;Melo et al, 2020;Miller et al, 2014;Pan et al, 2022;Smith et al, 2012). Meanwhile, immediate-early gene analyses indicate that the two regions have complementary roles in spatial tasks (Czajkowski et al, 2020;Frankland & Bontempi, 2005). In addition, neuronal recordings suggest that the hippocampus may encode and help distinguish contexts, while the retrosplenial cortex may enable behaviourally significant cues to identify the current context (Smith et al, 2012) or help predict future navigational decisions (Miller et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that a measurable behavioral output in a spatial exploration paradigm could be produced by a range of alternative brain networks. In a seemingly homogeneous population of animals, different spatial strategies might spontaneously emerge and develop [8]. In this paper we investigated the possibility of engaging a specific spatial memory circuit as a result of the training protocol used.…”
Section: Introductionmentioning
confidence: 99%